IMPROVEMENTS FOR UPLINK LONG TERM EVOLUTION (UL-LTE) IN HETEROGENEOUS NETWORK USING DYNAMIC SPECTRUM ALLOCATION TECHNIQUE - Othman N.I.; Ismail A.F.; Badron K.; Hashim W.; Pinardi S. (Academy and Industry Research Collaboration Center (AIRCC), 2023)
Several interference mitigation strategies can be used in LTE networks to meet the consumers' increasing need for faster data speeds. Dynamic Spectrum Allocation (DSA), which maintains spectrum in a converged radio system and distributes it across all participating radio terminals, is one of the most promising solutions. However, the fundamental obstacle to achieving increased network capacities is increased inter-cell interference. The aim of this paper is to analyse the effectiveness of a newly proposed DSA technique by comparing its bit error rate (BER) and throughput (TP) with a typical uplink LTE configuration. To maximise throughput in a heterogeneous network, the suggested DSA technique utilises the Nash Bargaining Solution (NBS) scheme, a cooperative game theory that could correlate with the bit error rate. The software tool GNU Radio, which offers signal-processing blocks to develop software-defined radios and signal-processing systems, was used to create the setups. After the simulations were performed, the BER values were recorded and compared, while the TP values were established and computed appropriately. According to the results, the uplink (UL-LTE) architecture with DSA has an improved TP and a lower BER value. As a result, spectral efficiency can also be improved 2022,International Journal of Computer Networks and Communications. All Rights Reserved.